Clinical Characteristics and Treatment of Irritable Bowel Syndrome in a Colombian Population: A Cross-Sectional Study - Daniel Andrés Hernández-Velásquez; Esteban Rodríguez-Martínez; Jhonathan David Montoya-Meneses; Juan Sebastián González-Ceballos; Katherin Mosquera-Pérez; Laura Patiño-Mazuera; Melissa González-Montoya; Andrés Gaviria-Mendoza; Jorge Enrique Machado-Alba (Adis, Springer Healthcare, 2023)
Abstract Background Irritable bowel syndrome (IBS) is a functional disorder that leads to abdominal pain; its diagnosis is based on Rome IV criteria (recurrent abdominal pain at least 1 day per week in the last 3 months with more than two of the following: related to defecation, associated with a change in stool frequency and/or with a change in stool appearance). Objective To characterize an outpatient population diagnosed with IBS in Colombia during 2017-2018. Methods A cross-sectional study based on a review of clinical records of patients with a primary diagnosis of IBS. A representative sample of 380 individuals was recruited from a population of 38,182 people with a new diagnosis of IBS from a drug-claim database. Sociodemographic, clinical (symptoms, type of IBS, alarm features, etc.), treatment (pharmacological or not), and follow-up variables (for those with additional medical care at 3-12 months) were analyzed. The diagnosis and treatment used in the consultation were compared with clinical guidelines. Results Most of the 380 patients were women (n = 238; 62.6%), and the mean age was 40.1 ± 15.0 years. None of the physicians recorded the Rome IV criteria in the medical records. Unclassified IBS was the most prevalent subtype (n = 311; 81.8%), and the main symptom was abdominal pain (n = 327; 86.1%). Only 73 patients (19.2%) had follow-up data. The most frequently used drugs were aluminum hydroxide (n = 203; 53.4%) and hyoscine N-butyl bromide (n = 200; 52.6%). Regarding drugs included in the clinical practice guidelines, 19 people received loperamide (5.0%), 3 received trimebutine (0.8%), and 1 received sertraline (0.3%). Conclusions The patients were diagnosed without clearly established criteria, and they were treated symptomatically with little follow-up.